A half-analytical elastic solution for 2D analysis of cracked pavements. (March 2018) - Nasser, H.; Chabot, A.
Highlights: A half-analytical solution for practical analysis of 2D cracked pavements. The specific modelling reduces of 1 dimension the all studied structure. Interface stresses between layers at crack edges have no singularity problems. A "shear layer" is added to the Winkler's springs for the soil modelling. Abstract: This paper presents a half-analytical elastic solution convenient for parametric studies of 2D cracked pavements. The pavement structure is reduced to three elastic and homogeneous equivalent layers resting on a soil. In a similar way than the Pasternak's modelling for concrete pavements, the soil is modelled by one layer, named shear layer, connected to Winkler's springs in order to ensure the transfer of shear stresses between the pavement structure and the springs. The whole four-layer system is modelled using a specific model developed for the analysis of delamination in composite materials. It reduces the problem by one dimension and gives access to regular interface stresses between layers at the edge of vertical cracks allowing the initial debonding analysis. In 2D plane strain conditions, a system of twelve-second order differential equations is written analytically. This system is solved numerically by the finite difference method (Newmark) computed in the free Scilab software. The calculus tool allows analysis of the impact of material characteristics changing, loads and locations of cracks in pavements on the distribution of mechanical fields. The approach with fracture mechanic concepts is well suited for practical use and for some subsequent numerical developments in 3D.